Massage Effectiveness In Reduce Labor Pain and Anxiety: Literature Review - Suci Lestari Putri, Kadek; Hafidz Ash-Shiddiqi, Muhammad; Nur Alpiah, Dini (Worldwide Research Publishing, 2024)
This research was conducted to determine the effectiveness of massage in reducing labor pain and anxiety during childbirth. Massage therapy aims to decrease anxiety by lowering cortisol levels, while also alleviating pain in the legs, back, muscles, and joints. A literature review method was employed, using the PICO framework to search relevant studies from databases such as Google Scholar and PubMed. A total of 89 journals were reviewed based on inclusion and exclusion criteria, focusing on pregnant women experiencing labor pain and anxiety. The results showed that massage, administered 2 to 3 times a week with a duration of 40 minutes per session, significantly reduced pain and anxiety levels (P < 0.001). Various massage techniques, including Swedish massage, antenatal massage, and intrapartum massage, demonstrated effectiveness in reducing pain intensity and enhancing emotional well-being. The findings highlight that massage therapy, as a non-pharmacological intervention, can serve as a safe, cost-effective, and beneficial alternative for pain and anxiety management during labor. This study provides valuable insights for healthcare professionals in optimizing maternal care and improving childbirth experiences.